Efficacy and Safety of AbobotulinumtoxinA for the Treatment of Hemiparesis in Adults with Lower Limb Spasticity Previously Treated With Other Botulinum Toxins: A Secondary Analysis of a Randomized Controlled Trial - Esquenazi, Alberto (PM R, 2020)
OBJECTIVE: To examine the safety and efficacy of abobotulinumtoxinA in patients previously treated with botulinum toxin type A (BoNT‐A) products other than abobotulinumtoxinA. DESIGN: Secondary analysis from a phase 3, double‐blind, single‐cycle, randomized, placebo‐controlled study. SETTING: Fifty‐two centers (11 countries). PATIENTS: Adults with spastic hemiparesis were randomized (1:1:1) to receive abobotulinumtoxinA 1000 U, 1500 U, or placebo in their affected lower limb. MAIN OUTCOME MEASUREMENTS: Muscle tone (6‐point Modified Ashworth Scale [MAS], 0‐5) for the gastrocnemius‐soleus complex (GSC); proportion of MAS responders (≥1‐point improvement); angle of catch (X(V3)) and spasticity grade (Y) for the GSC and soleus. Assessments were at weeks 1, 4, and 12 post‐injection. Only descriptive statistics are presented. RESULTS: Of 388 patients, 84 received previous BoNT‐A treatment (abobotulinumtoxinA 1000 U: N = 30; abobotulinumtoxinA 1500 U: N = 28; placebo: N = 26). At week 4, mean (SD) changes in MAS score in the GSC were − 0.8 (1.1), −0.9 (1.0), and − 0.4 (0.7) for abobotulinumtoxinA 1000 U, 1500 U, and placebo, respectively. Greater MAS responder rates were observed for abobotulinumtoxinA versus placebo at all time points. Mean (SD) changes (week 4) for abobotulinumtoxinA 1000 U, 1500 U, and placebo for X(V3) were: GSC, 8° (21), 6° (10) and 1° (7); soleus, 11° (21), 5° (9) and 0° (8), respectively; for Y: GSC, −0.4 (0.7), −0.6 (0.8) and − 0.0 (0.9); soleus, −0.5 (0.7), −0.5 (0.7) and − 0.1 (0.6), respectively. Safety data and adverse events were consistent with the overall known profile of abobotulinumtoxinA. CONCLUSIONS: Patients previously treated with other BoNT‐As showed improved muscle tone and spasticity at week 4 following abobotulinumtoxinA injection versus placebo. These findings suggest that abobotulinumtoxinA, at the recommended doses, has a good safety and efficacy profile in adults with lower limb spasticity who were previously treated with other BoNT‐A products.